2001
DOI: 10.1007/s001250100530
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of glucokinase mutations in Italian children with MODY. Influence on glucose tolerance, first-phase insulin response, insulin sensitivity and BMI

Abstract: Aims/hypothesis. The aim of this study was to assess the prevalence of glucokinase gene mutations in Italian children with MODY and to investigate genotype/phenotype correlations of the mutants. Methods. Screening for sequence variants in the glucokinase gene was performed by denaturing gradient gel electrophoresis and direct sequencing in 132 children with maturity onset diabetes of the young (MODY) and in 9 children with chronic fasting hyperglycaemia but without laboratory evidence for Type I (insulin-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…This GCK MODY prevalence is in line with those detected in southern European countries, particularly in France and in Italy, namely between 8% and 56% [25][27]. An analysis of the 3D structure of the protein mutants yielded evidence of structural perturbations, which supports the GCK MODY-causing nature of these mutations.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This GCK MODY prevalence is in line with those detected in southern European countries, particularly in France and in Italy, namely between 8% and 56% [25][27]. An analysis of the 3D structure of the protein mutants yielded evidence of structural perturbations, which supports the GCK MODY-causing nature of these mutations.…”
Section: Discussionsupporting
confidence: 83%
“…Massa et al [25] did not find an association between phenotype and genotype in GCK MODY patients. Two of our unrelated patients, M001 and M006, who both carried the p.Glu290X mutation, had a low birth weight but a different diabetic phenotype as evaluated by OGTT, FPIR tests and triglyceride level.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Among autoantibody-negative subjects, a significant number (∼23%) met the criteria for clinical diagnosis of maturity-onset diabetes of the young (MODY), i.e., two or three consecutive generations with hyperglycemia diagnosed before age 25 years (3,4). Alterations in at least six different genes cause MODY (3), with mutations of the glucokinase ( GCK ) and hepatocyte nuclear factor 1α ( HNF1 Α) genes accounting for up to 85% of MODY in Europe.…”
mentioning
confidence: 99%
“…In France, GCK mutations are the most common cause of MODY, with more than 60% of studied population carrying mutations in this gene [12,18,21]. GCK defects are also the first cause of MODY among Italian and Spanish patients [29,34]. However, studies in the United Kingdom [35] and Germany [5] found GCK mutations in only 11% and 8% of the series, respectively.…”
Section: Discussionmentioning
confidence: 99%